Valuing productivity loss due to absenteeism: Firm-level evidence from a Canadian linked employer-employee survey - Wei Zhang; Huiying Sun; Simon Woodcock; Aslam H. Anis (Health Economics Review, 2017)
In health economic evaluation studies, to value productivity loss due to absenteeism, existing methods use wages as a proxy value for marginal productivity. This study is the first to test the equality between wage and marginal productivity losses due to absenteeism separately for team workers and non-team workers. Our estimates are based on linked employer-employee data from Canada. Results indicate that team workers are more productive and earn higher wages than non-team workers. However, the productivity gap between these two groups is considerably larger than the wage gap. In small firms, employee absenteeism results in lower productivity and wages, and the marginal productivity loss due to team worker absenteeism is significantly higher than the wage loss. No similar wage-productivity gap exists for large firms. Our findings suggest that productivity loss or gain is most likely to be underestimated when valued according to wages for team workers. The findings help to value the burden of illness-related absenteeism. This is important for economic evaluations that seek to measure the productivity gain or loss of a health care technology or intervention, which in turn can impact policy makers' funding decisions.
Keywords: J31; D24; I12; I15; 330; Productivity loss; Absenteeism; Marginal productivity; Wage; Teamwork; Valuation